The development of agribusiness logistics as a factor of expansion the food and fiber market - Zhenishan, D.; Balkibayeva, А.М.; Gizzatzhanova, A.G. (BUKETOV BUSINESS REVIEW, 2017)
The article deals with the concept of «logistics» and «agribusiness logistics». It marked the role and importance of logistics in agribusiness food security. The basic principles and conditions of the logistics system is indicated. For such agrarian countries as Kazakhstan indepth study of agribusiness logistics and study it at the state level results from social needs is an important issue. The reason is that for local farmers to ensure availability of public services market, reducing intermediation between producers and consumers, the formation of stable prices of agricultural products, creation of direct links between the consumer and the rural entrepreneurs, improving the quality of socio-economic status of the rural population, the saturation of the internal domestic market production, reducing imports, transportation of agricultural products, providing quality products at affordable prices due to the expansion of marketing, services and other aspects are very important for agriculture. The article deals with the role of agricultural logistics in solving the above problems. Modern state agribusiness logistics in Kazakhstan is illuminated. A dynamic analysis of the share of individual groups and types of goods in the food industry of Kazakhstan's total imports and exports was conducted. According to the latest production of the most consumed types of food and their consumption were taken as a basis and their comparative analysis carried out. The level of self-secure on internal market is measured. The share of imports on certain types of food products is defined. On the basis of quantitative and qualitative analysis of food secure logistical problems in the field of agriculture is defined and the systematic proposals for their solution is offered.